Protective Effects of Intranasal Immunization with Recombinant Glycoprotein D in Pregnant BALB/c Mice Challenged with Different Strains of Equine Herpesvirus 1 - Fuentealba, Nadia Analia (2014)
Equine herpesvirus (EHV)-1 induces respiratory infection, neurological disorders and abortion in horses. Most of the currently available attenuated or inactivated vaccines against this infection are administered intramuscularly and only provide partial protection against the respiratory disease. The present study examines the effect of intranasal immunization with purified EHV-1 recombinant glycoprotein D (gD) in BALB/c mice followed by challenge with three different EHV-1 strains during early to mid-pregnancy. The induced viral infection was evaluated by virus isolation, DNA detection by polymerase chain reaction, histopathology and immunohistochemical localization of antigen in the lung, placenta and uterus. Non-immunized mice showed clinical signs of infection, positive virus isolation from lungs and uteri, and abortion induced by one of the virus strains. Endometrial lesions developed in some of these animals that have been described previously only in horses. Immunized mice and their offspring had no viral infection or typical lesions. Intranasally administered gD therefore induced partial or complete protection against three different EHV-1 strains in BALB/c mice.